AIR KELAPA SEBAGAI AGEN REHIDRASI: STUDI DENYUT NADI PEMULIHAN PADA MAHASISWA PENDIDIKAN OLAHRAGA - Rizky Alfareza Pratama; Andri Tria Raharja (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
Coconut water, a natural hydration agent, contains electrolytes and carbohydrates that help accelerate the body's recovery after physical activity. This study aimed to compare the effects of fresh coconut water and bottled coconut water on heart rate recovery in 12 students in the Sports Education Program at the University of Muhammadiyah East Kalimantan, selected based on certain characteristics. Participants were divided into three groups: a control group (mineral water), an experimental group (fresh coconut water), and an experimental group (bottled coconut water). Heart rate was measured at 2, 4, and 6 minutes after a 400-meter run. Analysis using one-way ANOVA and repeated measures ANOVA showed that fresh coconut water significantly accelerated heart rate recovery compared to bottled coconut water. Therefore, fresh coconut water is more effective as a natural hydration for body recovery after physical activity.